Penerapan Nilai-Nilai Kebangsaan Bersumber dari Pancasila dan UUD 1945 dalam Meninjau Strategi Manajemen Sekuriti pada PT. PLN (Persero) Guna Meningkatkan Kepuasan Pemenuhan Kebutuhan Listrik untuk Menyejahterakan Masyarakat Indonesia - Annisa Karenina Ajie; Edy Soesanto; Luthfia Salsabilla (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
PLN is a state-owned company which operates in the fields of electricity generation, electricity supply, telecommunications, finance and maintenance services. In accordance with the existing electricity supply law, the Indonesian state-owned company which is given the authority to manage the electricity industry, starting from the industrial, housing, business, government office and public street lighting sectors is PT. PLN. Apart from that, PT. PLN is also obliged to improve the welfare of the Indonesian people by fulfilling electricity needs in accordance with the 5th principle of Pancasila. The method used in this research is the literature review journal method. This research is to describe the extent to which national values originating from Pancasila and the 1945 Constitution are implemented in PT's security management strategy. PLN to increase satisfaction with meeting the electricity needs of the Indonesian people. The aim of this research is to analyze the implementation of security management strategies at PT. PLN is based on national values, namely the 5th principle of Pancasila and Law Number 30 of 2009 concerning Electricity Articles 28a and 28b. PT. PLN as a state-owned business actor which is fully obliged and responsible for its design in accordance with existing laws, must ensure that the security management system implemented by this company covers security and safety aspects in its operations.